2005
DOI: 10.1111/j.1365-2788.2005.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

What am I doing in Timbuktu: person–environment picture recognition for persons with intellectual disability

Abstract: Background The aim of this study was to examine the effects of familiarity of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Recall may as a consequence depend on familiarity processes (implicit) which results in retrospective memory errors if the task requires recall of distinct pieces of information (e.g., Danielsson, Rönnberg, & Andersson, 2006). PM tasks with low demand on strategic memory processing such as planning, e.g., tasks with salient PM cues and low demand from the ongoing task, can thus be predicted to be essential for PM performance in persons with intellectual disability in particular.…”
Section: Performance In Persons With Intellectual Disabilitymentioning
confidence: 99%
“…Recall may as a consequence depend on familiarity processes (implicit) which results in retrospective memory errors if the task requires recall of distinct pieces of information (e.g., Danielsson, Rönnberg, & Andersson, 2006). PM tasks with low demand on strategic memory processing such as planning, e.g., tasks with salient PM cues and low demand from the ongoing task, can thus be predicted to be essential for PM performance in persons with intellectual disability in particular.…”
Section: Performance In Persons With Intellectual Disabilitymentioning
confidence: 99%
“…Photographs are ecologically interesting since they are also used for purposes of augmentative and alternative communication for the learning disability group (cf. Danielsson, Rönnberg & Andersson, 2004, 2006). Kroll et al (1996) demonstrated low performance for individuals with left or right hippocampal brain damage for one type of face drawing stimuli, and argued that many and complicated facial features with high similarity would cause more errors to be made.…”
Section: Introductionmentioning
confidence: 99%
“…La idea de implementar la enseñanza de la fotografía como medio para la adquisición de herramientas en el reconocimiento facial, parte de una necesidad lúdica y práctica, para que las personas con discapacidad intelectual puedan adquirir herramientas sociales. En su mayoría los estudios científicos utilizan fotografías como una herramienta de comunicación (Danielsson, et al, 2006), o la evaluación de cursos de fotografía, sin ligarlo a la psicología (Edrisinha, O'Reilly, Choi, Sigafoos y Lancioni, 2011). La idea de los autores parte de la unión de estos dos elementos, en donde ellos mismos puedan crear sus herramientas (fotografías) y observar si un curso base de fotografía puede también servir para el reconocimiento de emociones, haciéndolo un trabajo original en el ámbito de investigaciones comprobables.…”
Section: Introductionunclassified